2020
DOI: 10.1186/s12957-020-01923-7
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E mutation, BRAF-activated long non-coding RNA and miR-9 expression in papillary thyroid carcinoma, and their association with clinicopathological features

Abstract: Background: The incidence of thyroid cancer is increasing worldwide. This study investigated the association of Btype RAF kinase (BRAF) V600E mutation status, the expression of BRAF-activated long non-coding RNA (BANCR) and microRNA miR-9, and the clinicopathological features of papillary thyroid carcinoma (PTC). Methods: Clinicopathological data for PTC patients (n = 51) diagnosed and treated between 2018 and 2019 were collected. Carcinoma and adjacent normal tissue samples were analyzed for the presence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…With the emerging understanding of molecular genetics in thyroid cancer, several specific molecular events in PTC have been identified that assist in the diagnosis and prognostic evaluation of PTC patients [11][12][13]. The Btype Raf kinase (BRAF) V600E mutation was found to be the most important candidate biomarker for PTC diagnosis because of its high prevalence and high specificity [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…With the emerging understanding of molecular genetics in thyroid cancer, several specific molecular events in PTC have been identified that assist in the diagnosis and prognostic evaluation of PTC patients [11][12][13]. The Btype Raf kinase (BRAF) V600E mutation was found to be the most important candidate biomarker for PTC diagnosis because of its high prevalence and high specificity [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The 2 reviewers were in agreement regarding study eligibility. The earliest study was published in May 2010 [15] and the latest in June 2020 [16]. The included studies were from 7 countries: China (n = 20), Serbia (n = 2), Lithuania (n = 1), South Korea (n = 1), Taiwan (n = 1), Turkey (n = 1), and the USA (n = 1).…”
Section: Analysis Resultsmentioning
confidence: 99%
“…For initial genome screening, 4 studies [15,[20][21][22] performed microarray, and 1 study [17] used Solexa sequencing, followed by qRT-PCR to validate results. However, of all the rest of the studies 21 performed qRT-PCR [16,19,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]] and 1 study performed northern blotting [18] to quantify miRNA expression for a priori selected miRNAs from the literature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the formerly mentioned study, the presence of BRAF V600E mutation has been associated with higher probability of BANCR up-regulation. Patients with BRAF V600E mutation, over-expression of BANCR and down-regulation of miR-9 have been shown to need earlier surgical management particularly total thyroidectomy in primary surgery in order to decrease tumor recurrence ( Shi et al, 2020 ). Supplementary Table 2 demonstrates the observed effects of BANCR dysregulation in clinical settings.…”
Section: Clinical Studiesmentioning
confidence: 99%